Pneumatic and Optical Characterization and Optimization of Hydrogen Injectors for Internal Combustion Engine Application - Rolke, Philipp; Broja, D.; Fink, A.; Maaß, J.; Nett, O. (Frontiers in Mechanical Engineering, 2022)
To achieve future emission targets for internal combustion engines, the use of hydrogen gas generated by renewable energy sources (known as “green” hydrogen) instead of fossil fuels plays a key role in the development of new combustion based engine concepts. For new hydrogen engine generations, there are different challenges concerning the injector functionality. On the on hand the requested amount of hydrogen gas amount needs to be provided in time and on the other hand accurately metered in order to provide an appropriate mixing formation quality inside the combustion chamber. This work discusses deep injector analysis techniques with pneumatic and optical approaches for an improved overall understanding of functionality and effects caused by operation with a gaseous fuel. A metering technique for gas flow characterization and, for test simplification, a comparison for the behavior of hydrogen with helium and nitrogen as possible surrogate gases will be introduced. Furthermore, this contribution will focus on the usability of helium instead of hydrogen for the determination of spray properties. This is shown by comparison of spray propagation images which were observed with schlieren-technique in a pressure vessel. In a next step, the usage of spray-guiding devices to improve the global gas distribution during the injection period, will be discussed.